Efficacy of the Baseline Complex Treatment in Achieving the Target Blood Pressure Values, Dynamics of Brachial Artery Remodeling and Endothelial Dysfunction in Patients with Acute Myocardial Infarction with ST Segment Elevation and Comorbid Arterial Hypertension (Prospective Observation During Two Years) - Denesyuk О. (Львівський клінічний вісник)
Introduction. In patients with arterial hypertension, the constant increase in blood pressure is associated with vascular remodeling and structural decrease in the lumen of the arteries as a result of thickening of the medial layer. This problem is particularly acute in patients with myocardial infarction, which already presents endothelial dysfunction. Therefore, the study of the effect of the basic comprehensive treatment on achieving the target blood pressure values, the dynamics of brachial artery remodeling and endothelial dysfunction in patients after acute myocardial infarction with comorbid arterial hypertension is extremely relevant. The aim of the study. To determine the effectiveness of basic complex treatment in achieving target blood pressure indicators, dynamics of shoulder artery remodeling and endothelial dysfunction in patients with acute myocardial infarction with ST segment elevation with comorbid arterial hypertension for two years. Materials and methods. 22 patients were examined after acute myocardial infarction with ST segment elevation in conjunction with hypertension. The transferred second myocardial infarction in history was determined in 7 (31.8 %), cardiac insufficiency of IIII functional classes was determined in 100.0 % of cases. Patients received a general clinical examination: ECG, echocardiography, the lipid blood spectrum was determined, and reactive hyperemia was used in doppler agitation of the brachial artery. Treatment continued for two years: inhibitor angiotensin converting enzyme perindopril was used at a dose of 5.0-10.0 mg/day, βblocker biosoprolol 5.0-10.0 mg/day, hypolipidemic drug atorvastatin 20.0 mg/day and acetylsalicylic acid 75.0 mg/day. Results. In the examined patients, a significant increase in the thickness of the intimamedia complex and the reduction of endothelialdependent vasodilatation were found, indicating the development of the remodeling of the brachial artery and endothelial dysfunction. After two years of treatment, positive dynamics was observed. The target level of blood pressure was reached at 100.0 %. There was a significant decrease in the thickness of the intima media complex, an increase in of endothelialdependent vasodilatation and improvement of their degrees, indicating a positive dynamics of the shoulder artery remodeling, endothelial dysfunction under the influence of therapeutic measures. Conclusions. In patients after acute myocardial infarction in combination with hypertension, the achievement of the target level of blood pressure with optimal twoyear treatment gradually increased and in 6 months was determined at 70.0 %, after 12 months at 93.8 %, after 24 months at 100.0 %. In the examined patients, the treatment determined a significant increase in the thickness of the intimamedia complex and decreased endothelialdependent vasodilatation of the brachial artery. After treatment in 6, 12 and 24 months, a tendency towards the improvement in the brachial artery remodeling and endothelial dysfunction was determined. An individual analysis of the extent of disturbances in the brachial artery remodeling indices, despite the small number of individuals examined, showed a tendency to decrease the number of patients with II (moderate) thickness of the intimamedia complex and III (significant) degree of endotheliumdependent vasodilatation as a result of a transition to a less pronounced degree, which testifies to the positive dynamics of the brachial artery remodeling, endothelial function and the efficacy of the treatment.